2005
DOI: 10.1016/j.jacc.2004.09.081
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric Quantitative Analysis of Tissue Characteristics of Coronary Plaques After Statin Therapy Using Three-Dimensional Integrated Backscatter Intravascular Ultrasound

Abstract: Statin therapy reduced the lipid component in patients with stable angina without reducing the degree of stenosis. Three-dimensional IB IVUS offers the potential for quantitative volumetric tissue characterization of coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
139
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(147 citation statements)
references
References 36 publications
7
139
0
1
Order By: Relevance
“…The observed plaque stabilization effect induced by statins might potentially be attributed to pleomorphic effect including a decrease in the lipid content of plaques, a reduction in the inflammatory burden and an improvement in endothelial function; all promoting a more stable phenotype (67)(68)(69)(70)(71). Notwithstanding, most evidence in this regard remains inconclusive or speculative.…”
Section: Effect Of Statins On Cacmentioning
confidence: 99%
“…The observed plaque stabilization effect induced by statins might potentially be attributed to pleomorphic effect including a decrease in the lipid content of plaques, a reduction in the inflammatory burden and an improvement in endothelial function; all promoting a more stable phenotype (67)(68)(69)(70)(71). Notwithstanding, most evidence in this regard remains inconclusive or speculative.…”
Section: Effect Of Statins On Cacmentioning
confidence: 99%
“…The Kawasaki group at the Gifu University Graduate School of Medicine in Japan has published studies using integrated backscatter signals from the radiofrequency signal of ultrasound, and based on the backscatter IVUS image, they have used colour to code different components of plaque. 8,9 Another established technique developed by Volcano Corporation® (Rancho Cordova, CA, US) uses radiofrequency signals to determine plaque composition. 10 In this technique, the distortion of radiofrequency signal by the plaque is passed through an algorithm, which is then colour-coded and superimposed on the grey image -a technique commercialised as 'Virtual Histology intravascular ultrasound' (VH-IVUS).…”
Section: Characterisation Of Atherosclerosismentioning
confidence: 99%
“…Using virtual histology (VH)-IVUS, the TRUTH study reported that fibrous plaques regressed more in patients in whom statin treatment led to the regression of coronary plaque than in those in whom this increased. 21) Moreover, in an investigation of changes in plaque components using IB-IVUS in patients with stable angina pectoris, Kawasaki, et al 7) reported that the internal administration of atorvastatin (20 mg) could cause plaque lipid components to be replaced by fibrous components. We demonstrated that statin treatment caused reductions in fibrous components, in contrast to findings of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…5,6) Plaque stability can potentially be achieved by a change in plaque contents, such as the removal of lipids from the lipid-rich plaque and an increase in its fibrous tissue, without an improvement in the degree of plaque volume. 7) Using serial IVUS examinations in patients with stable angina pectoris, the Study of Coronary Atheroma by Intravascular Ultrasound: Effect of Rosuvastatin versus Atorvastatin (SATURN) trial revealed that water-soluble and lipid-soluble statins provided comparable benefits in reducing plaque volume. 8) These statins have different chemical structures and show differences in their cell-membrane permeability.…”
mentioning
confidence: 99%